Future Directions in Strategic Brand Management Research Using Bibliometric Analysis: A Decade Review - Indriarti, Resti; Hurriyati, Ratih; Dirgantari, Puspo Dewi; Harisandi, Prasetyo (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2024)
This research aim is to examine future directions in strategic brand management research through a bibliometric computational mapping analysis using VOS viewer. Publish or Perish reference manager application is used to retrieve the Google Scholar database in order to fulfill research data. The title and abstract of the article are used to provide guidance on the search process based on the keywords "Strategic Brand Management". The results showed 997 relevant articles. The search for publication data used as study material was carried out in the last ten years (2013-2023). The results also showed that there are two larger circles comparing others, namely “brand loyalty” and “business strategy”. The term “brand loyalty” is associated with 15 links, 33 total link strength, and 30 occurrences, while the term “business strategy” is associated with 10 links, 33 total link strength, and 31 occurrences. The results of strategic brand management research in the last ten years show a declining trend, from 104 publications to 61 publications. There were only increase a little bit in 2015, from 104 publications to 115 publications, and increase in 20203, from 80 publications to 93 publications. Based on a downward trend, publications on strategic brand management in the last ten years were dominated by 2015 (115 publications). The results of this study are expected to inspire and develop the articles of related terms in the future.